Pendidikan Formal Bagi Masyarakat Desa Kayu Bulan Kecamatan Kapuas Tengah Kabupaten Kapuas - Alexandro, Rinto; Putri, Windy Utami (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to find out how formal education is for the Community of Desa Bulan Bulan Kapuas Tengah District Kapuas District. While the type of research is qualitative research. The subjects of the study were the village head, parents of school age children and school age children. Data collection techniques are in-depth interviews, observation and documentation. The data analysis technique used in this study was Odel Miles and Huberman. Activities in data analysis are data reduction, data display, and conclusion drawing / verification. The results of this study indicate that formal education for the people of Kayu Bulan Village, Kapuas Tengah District, Kapuas Regency, is a place to get knowledge and benefit young people to improve their quality. The supporting factors for formal education in Kayu Bulan Village are the support from parents to children to attend formal education, the existence of buildings, textbooks, and equipment and costs needed at school. While the inhibiting factor they feel is the mindset of children who do not consider school is something serious, there are various delinquents of adolescents who have begun to influence children in Kayu Bulan Village and the emergence of a child's laziness to attend formal education due to teachers who are disliked by children, and an invitation from parents to come to work